Development of a double-antigen sandwich ELISA for rapid and accurate detection of antibodies against Capripoxvirus - Wanying Wang; Zhengwang Shi; Juncong Luo; Huancheng Liao; Lu Feng; Yuqian Zhu; Yongyu Lin; Xintai Shi; Fan Zhang; Tao Xi; Jie Chen; Hong Tian; et al. (Microbiology Spectrum)
ABSTRACT Lumpy skin disease, goatpox, and sheeppox have rapidly spread in many countries, leading to the emergence of new mutant strains that have caused substantial damage and posed significant threats to animal husbandry in endemic areas. Effective surveillance and disease control necessitate a simple and precise diagnostic method for detecting antibodies against Capripoxvirus (CaPV). In the present study, a double-antigen sandwich enzyme-linked immunosorbent assay (DAgS-ELISA) based on the 122 protein expressed early in viral replication and with high immunogenicity and conservation was developed to detect antibodies against lumpy skin disease virus (LSDV), goatpox virus (GTPV), and sheeppox virus (SPPV). The receiver operating characteristic (ROC) was performed to identify the best threshold value using 109 negative and 57 positive samples. The established test exhibited an area under the curve (AUC) of 0.997, and the test achieved a diagnostic sensitivity of 94.7% and a specificity of 96.3% when the S/P value threshold was set at 0.304. This method can detect the positive standard serum at a dilution of 1:32. The performances of the DAgS-ELISA were highly consistent with the commercial kit in testing 150 clinical serum samples, which were very similar (kappa value = 0.759). Moreover, the analysis of antibody dynamics revealed that the results exhibited higher sensitivity in early detection of total antibodies compared with the commercial kit. In conclusion, the DAgS-ELISA method demonstrated excellent repeatability, user-friendliness, and the ability to provide early detection of CaPV antibodies, which is highly suitable for epidemiological studies and evaluation of vaccine-induced antibody responses.IMPORTANCEIn this study, a double-antigen sandwich ELISA was developed based on the 122 protein with high immunogenicity and conservation during early viral replication, aiming to detect antibodies against Capripoxvirus. This method features high sensitivity and specificity, is cost-effective, simple, reproducible, and suitable for extensive testing. It can detect antibodies at an early phase and serves as a powerful tool for epidemic monitoring, prevention, and control.